CLINICAL CHARACTERISTICS OF POSTERIOR TEETH INDICATED FOR INLAY/ONLAY RESTORATIONS USING 3D- PRINTED TERA HARZ TC-80DP RESIN MATERIAL AT CAN THO UNIVERSITY OF MEDICINE AND PHARMACY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Restoration of posterior teeth with Class II lesions remains a challenge in restorative dentistry, data on the clinical characteristics of posterior teeth indicated for inlay/onlay restoration using 3D-printed resin Tera Harz TC-80DP are still limited. . Objective: To describe the clinical characteristics of posterior teeth indicated for inlay/onlay restorations fabricated from 3D-printed resin Tera Harz TC-80DP at Can Tho University of Medicine and Pharmacy Hospital. Materials and Methods: A cross-sectional descriptive study was conducted on 48 posterior teeth presenting with Class II carious lesions at Can Tho University of Medicine and Pharmacy Hospital. Results: The primary reason for dental visits was routine check-ups (27.1%), followed by toothache (25%) and dental caries (22.9%). Most patients reported brushing their teeth at least twice daily (87.5%), with a statistically significant difference among occupational groups (p < 0.05). Class II cavities of moderate severity (grade 2) predominated (60.4%), with the majority of lesions located at the mesio-occlusal surface (77.1%). Teeth with grade 3 Class II cavities exhibited a higher prevalence of preoperative dentin hypersensitivity compared to grade 2 (47.4% vs. 20.7%); however, the difference was not statistically significant (p > 0.05). Conclusion: In this study sample, teeth indicated for inlay/onlay restorations using 3D-printed resin Tera Harz TC-80DP were predominantly Class II cavities of moderate severity. Most patients demonstrated good oral hygiene practices and attended routine dental check-ups. Grade 3 Class II cavities tended to be associated with a higher incidence of dentin hypersensitivity prior to treatment.
Keywords: inlay/onlay, 3D-printed Tera Harz TC-80DP resin, Class II cavity, posterior teeth.